Enhanced mechanical, thermal, and morphological properties of waste PET plastics reinforced with coated biodegradable kenaf fibers for infrastructure applications - Owen M.M.; Wong L.S.; Achukwu E.O.; Saharudin M.S.; Akil H.M. (Elsevier Ltd, 2025)
The surge in polyethylene terephthalate (PET) plastic bottle production has led to a rise in waste PET plastics. Recycling these waste PET plastics for infrastructural purposes offers a feasible solution to curb environmental pollution and the climatic impact caused by dumping vast quantities into landfills. Hence, efforts have been directed towards creating waste PET plastic composites reinforced with coated biodegradable natural kenaf fibers for infrastructural use. In the current research, waste PET plastic bottles (WPET) were processed into value-added composites compounded with coated kenaf natural fibers (CK) using the twin-screw extruder (TSE) and compression molding machines at an optimized temperature of 250 C with a constant fiber weight percentage and epoxy coating concentration of 10 wt% and 25 % conc., respectively. The composites underwent analysis for mechanical, thermal, and microstructural properties based on relevant ASTM standards. Results indicate significant enhancement in surface interactions/interface and improved mechanical and thermal properties of kenaf fibers due to epoxy coating. Thermal stability improved to 409.4 C from 397.0 C due to coating, with a higher melting peak of 252.8 C. These materials exhibit suitability for energy and building infrastructural applications, presenting an alternative, economical, and sustainable approach to managing the abundance of waste PET plastic bottles. ? 2024 Elsevier Ltd